Estación parque de conexión multimodal de transporte terrestre: C.A.N.: Plan parcial de renovación urbana nuevo C.A.N. (2017)
From the approach of the development of the urban piece of the National Administrative Center CAN, begins to produce a spatial, structural and landscape solution for the sector. Based on important aspects such as the development of buildings in height and business and financial, which have been presented on one of the most important corridors for the city of Bogota as is Av. Calle 26. According to the existing plans for this area, and the proposal to move the National Ministries that are currently there, to the city center, thus freeing the space occupied for new plans and developments in the future.